2008
DOI: 10.7863/jum.2008.27.6.855
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Retention of a Vascular Endothelial Growth Factor Receptor 2 (VEGFR2)-Targeted Ultrasonographic Contrast Agent and the Level of VEGFR2 Expression in an In Vivo Breast Cancer Model

Abstract: The magnitude of the molecular ultrasonographic signal from a VEGFR2-targeted UCA retained by tissue correlates with VEGFR2 expression. These results validate the use of molecular ultrasonography for in vivo detection and quantification of VEGFR2 expression in this breast cancer model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…They also used VEGFR2-and CD105-targeted microbubbles to detect angiogenesis in a subcutaneous tumor model. Lyshchik et al22 and Lee et al21 showed that there was a positive correlation between the ultrasound signal obtained from VEGFR2-targeted microbubbles (Target-Ready MicroMarker coupled to antibody clone Avas 12a1) and the level of expression of VEGFR2 in the endothelium of breast tumors. In a similar study, Rychak et al 23 performed high frequency ultrasound imaging of VEGFR2 in a subdermal mouse melanoma model with the same anti-Flk-1 antibody coupled to a commercial preparation of biotinylated microbubbles.…”
mentioning
confidence: 97%
“…They also used VEGFR2-and CD105-targeted microbubbles to detect angiogenesis in a subcutaneous tumor model. Lyshchik et al22 and Lee et al21 showed that there was a positive correlation between the ultrasound signal obtained from VEGFR2-targeted microbubbles (Target-Ready MicroMarker coupled to antibody clone Avas 12a1) and the level of expression of VEGFR2 in the endothelium of breast tumors. In a similar study, Rychak et al 23 performed high frequency ultrasound imaging of VEGFR2 in a subdermal mouse melanoma model with the same anti-Flk-1 antibody coupled to a commercial preparation of biotinylated microbubbles.…”
mentioning
confidence: 97%
“…There is considerable evidence that targeted microbubbles can be used to detect the presence of various biomarkers in vivo, with the majority of studies suggesting that a positive correlation exists between the magnitude of the molecular ultrasound signal and a measure of the biomarker's expression [12]. They are limited, however, in their ability to say with certainty what portion of the bound bubbles are actually detected and whether the microbubble binding and detection is a consistent and quantitative assessment of molecular expression.…”
Section: Introductionmentioning
confidence: 98%
“…Acoustic quantification has been assessed against independent (non-acoustic) methods, such as semi-quantitative immunohistochemistry and fluorescence immunohistochemistry (Behm et al 2008;Kaufmann et al 2007b;Korpanty et al 2007;Lee et al 2008;Leong-Poi et al 2005;Liu et al 2011;Mancini et al 2013;Palmowski et al 2008Palmowski et al , 2009Weller et al 2003;Xie et al 2011), illustrating at best the semiquantitative capability of the imaging technique. Only a handful of studies have used highly quantitative independent assays to assess acoustic quantification; these included quantitative radioactive assay (Bin et al 2008), quantitative fluorescence imaging (Saini et al 2013), quantitative chemiluminescence immunoblotting (Deshpande et al 2011;Lyshchik et al 2007) and quantitative fluorescence immunohistochemistry (Bachawal et al 2013).…”
Section: Introductionmentioning
confidence: 99%